Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Alright, let's solve the given equation step-by-step.
We start with the equation:
[tex]\[ x^2 + \frac{33}{8} x = \frac{9}{8} x \][/tex]
First, let's simplify the equation by moving all terms to one side:
[tex]\[ x^2 + \frac{33}{8}x - \frac{9}{8}x = 0 \][/tex]
Combine the like terms:
[tex]\[ x^2 + \left(\frac{33}{8} - \frac{9}{8}\right)x = 0 \][/tex]
Simplify the coefficient of [tex]\( x \)[/tex]:
[tex]\[ x^2 + \frac{24}{8}x = 0 \][/tex]
[tex]\[ x^2 + 3x = 0 \][/tex]
Next, we factor the equation:
[tex]\[ x(x + 3) = 0 \][/tex]
Now, we set each factor equal to zero to find the solutions:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x + 3 = 0 \Rightarrow x = -3 \)[/tex]
Thus, the solutions to the equation are:
[tex]\[ x = 0, -3 \][/tex]
Let's verify these solutions by substituting them back into the original equation.
1. Substitute [tex]\( x = 0 \)[/tex] into the original equation:
[tex]\[ 0^2 + \frac{33}{8}(0) = \frac{9}{8}(0) \][/tex]
[tex]\[ 0 = 0 \][/tex]
This is true.
2. Substitute [tex]\( x = -3 \)[/tex] into the original equation:
[tex]\[ (-3)^2 + \frac{33}{8}(-3) = \frac{9}{8}(-3) \][/tex]
[tex]\[ 9 - \frac{99}{8} = -\frac{27}{8} \][/tex]
Convert 9 to a fraction with denominator 8:
[tex]\[ \frac{72}{8} - \frac{99}{8} = -\frac{27}{8} \][/tex]
[tex]\[ \frac{72 - 99}{8} = -\frac{27}{8} \][/tex]
This is true.
Therefore, the roots of the equation [tex]\( x^2 + \frac{33}{8} x = \frac{9}{8} x \)[/tex] are:
[tex]\[ x = 0, -3 \][/tex]
We start with the equation:
[tex]\[ x^2 + \frac{33}{8} x = \frac{9}{8} x \][/tex]
First, let's simplify the equation by moving all terms to one side:
[tex]\[ x^2 + \frac{33}{8}x - \frac{9}{8}x = 0 \][/tex]
Combine the like terms:
[tex]\[ x^2 + \left(\frac{33}{8} - \frac{9}{8}\right)x = 0 \][/tex]
Simplify the coefficient of [tex]\( x \)[/tex]:
[tex]\[ x^2 + \frac{24}{8}x = 0 \][/tex]
[tex]\[ x^2 + 3x = 0 \][/tex]
Next, we factor the equation:
[tex]\[ x(x + 3) = 0 \][/tex]
Now, we set each factor equal to zero to find the solutions:
1. [tex]\( x = 0 \)[/tex]
2. [tex]\( x + 3 = 0 \Rightarrow x = -3 \)[/tex]
Thus, the solutions to the equation are:
[tex]\[ x = 0, -3 \][/tex]
Let's verify these solutions by substituting them back into the original equation.
1. Substitute [tex]\( x = 0 \)[/tex] into the original equation:
[tex]\[ 0^2 + \frac{33}{8}(0) = \frac{9}{8}(0) \][/tex]
[tex]\[ 0 = 0 \][/tex]
This is true.
2. Substitute [tex]\( x = -3 \)[/tex] into the original equation:
[tex]\[ (-3)^2 + \frac{33}{8}(-3) = \frac{9}{8}(-3) \][/tex]
[tex]\[ 9 - \frac{99}{8} = -\frac{27}{8} \][/tex]
Convert 9 to a fraction with denominator 8:
[tex]\[ \frac{72}{8} - \frac{99}{8} = -\frac{27}{8} \][/tex]
[tex]\[ \frac{72 - 99}{8} = -\frac{27}{8} \][/tex]
This is true.
Therefore, the roots of the equation [tex]\( x^2 + \frac{33}{8} x = \frac{9}{8} x \)[/tex] are:
[tex]\[ x = 0, -3 \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.